Antibody Titers Following Hepatitis B Vaccination in Health Care Workers in Khartoum State, Sudan - Ahmed-Abakur, Eltayib Hassan; Obaid, Amal; Abrahim-Holi, Mohamed Ahmed (International Journal of Medical and Health Sciences Research, 2014)
Hepatitis B vaccination is the most effective measure to prevent HBV infection and its consequences. The best strategy to eradicate HBV infection is a universal vaccination program. This study was a descriptive cross sectional study aimed at evaluating the efficiency of HBV vaccine in term of anti-HBs Ab level among vaccinated health care workers (HCWs) in Bahri Teaching Hospital, Khartoum state, Sudan. Ninety HCWs agreed to participate in this study, HBV antibody level (quantitative antibody) against HBsAg were measured using ELISA technique. The majority of study population 66 (73.33%) were aged (21-30 years), the active age groups (21-30) and (31-40) revealed remarkable reduction of HBsAb titer, 29 (43.93%) and 11 (55%), respectively. A total of 49 (54.4%) participants showed antibody titers above 10 IU/mL, 14 (15.6%) of them revealed strong response with anti-HBs Ab titers >100 IU/mL while HBsAb titers less than 10 IU/mL was detected in 41(45.6%) participants. A total of 83(92.22%) of the study population had the vaccine dose at proper interval whereas 7(7.78%) had the vaccine at irregular time. Eighteen18 (27.3%) of the participants who had the vaccine less than 5 years ago and 22 (91.7) of candidates who received the vaccine more than 5years ago did not respond to vaccine. Sixty-six (66; 73.33%) of the entire participants were females and 24 (26.67%) were males, out of which 28(42.2%) and 13(54.2%) of male and female, respectively fail to develop anti-HBsAb titer 10 IU/mL. Conclusion: this study revealed that other non immunological factors influence the outcome of vaccination; interval after vaccination and chronic disease were found to be significantly correlated (P<0.05) with antibody titers following hepatitis B vaccination.